Gunnar Jungner and the Principles and Practice of Screening for Disease - Lars Jungner; Ingmar Jungner; Martin Engvall; Ulrika von Döbeln (MDPI AG, 2017)
We present a biography of Gunnar Jungner, one of the authors of the Principles and Practice of Screening for Disease by JMG Wilson and G Jungner, published by the WHO in 1968. This publication contains ten criteria, which are still consulted, when a new disorder is evaluated for inclusion in a screening program. Gunnar Jungner was a Swedish MD, PhD, specialized in Clinical Chemistry, born in Sweden in 1914. In 1961 he built an automated instrument for the analysis of different components in plasma, with the aim to detect diseases in presumably healthy individuals, to enable start of treatment at an early disease stage. This first automated instrument for Clinical Chemistry in Sweden was used in a screening project, where 90 000 seemingly healthy individuals were included. The study was discussed extensively and he was invited to present the results at different international meetings, where he also met JMG Wilson. Gunnar Jungner developed the instrument further together with his brother Ingmar and the Swedish gas company AGA. The brothers also established an out-patient ward in Stockholm, where people could come for health screening.